Предложения по построению перспективных сетей доступа на основе концепции платформы сверхширокополосной беспроводной технологии передачи данных - Шостко, И. С. (Проблеми телекомунікацій, 2010)
The article represents a suggestion to combine of the access functions to the user network and the information system "smart house” under one module called the Multiple Play RGW gateway. Wireless interfaces based on a technology of common UWB radio platform in uprated gateway a used to transmit voice, data and signals and to control various terminal equipment.
Keywords: сверхширокополосные сигналы; многополосное ортогональное частотное разделение; шлюз Multiple Play RGW